2007
DOI: 10.1016/j.jasms.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sulfopeptide fragmentation in electron-capture and electron-transfer dissociation

Abstract: Sulfopeptides can be misassigned as phosphopeptides because of the isobaric nature of the sulfo-and the phosphomoieties. Instruments having the ability to measure mass with high accuracy may be employed to distinguish these moieties based on their mass defect (the sulfo-group is 9 mmu lighter than the phosphomoiety). However, the assignment of the exact site(s) of post-translational modification is required to probe biological function. We have reported earlier that peptides with identical sequences containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 28 publications
2
64
0
Order By: Relevance
“…There has been some discussion about the misidentification of phospho-and sulfopeptides because sulfopeptides also display an 80-Da mass increase (22). There are several reasons that render it unlikely that sulfated sites instead of phosphorylation sites were determined in our study.…”
Section: Identification Of Flagellar Phosphopeptides By Nlc-esi-msmentioning
confidence: 91%
“…There has been some discussion about the misidentification of phospho-and sulfopeptides because sulfopeptides also display an 80-Da mass increase (22). There are several reasons that render it unlikely that sulfated sites instead of phosphorylation sites were determined in our study.…”
Section: Identification Of Flagellar Phosphopeptides By Nlc-esi-msmentioning
confidence: 91%
“…Further, it has been demonstrated that sulfopeptides complexed to sodium ions were protected from fragmentation using positive mode electron capture/transfer dissociation (ECD/ETD) (45). Here, we explored if sodium ion complexation could be a feasible way of enhancing the stability of sulfate glycan substituents in positive mode MS/MS.…”
Section: Analysis Of Heavy Chain Cs Cross-linking Glycopeptides-by Trmentioning
confidence: 99%
“…All of the following peptides were provided by Protea Biosciences Inc. (Morgantown, WV, USA): the phosphorylated and non-phosphorylated forms of angiotensin II, cholecystokin (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and calcitonin (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29); the sulfated and non-sulfated forms of cholecystokinin (26)(27)(28)(29)(30)(31)(32)(33), leuenkephalin, and hirudin. Methanol (HPLC grade), ammonium hydroxide, and glacial acetic acid were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Preparation Of Peptidesmentioning
confidence: 99%
“…To achieve improved ionization efficiency and modification retainment of highly acidic sulfonated peptides in ECD, charge enrichment through the formation of a divalent metal cation-peptide complex is necessary. In a similar experiment, Medzihradszky et al investigated the labile nature of sulfonated peptides that contained only one basic amino acid employing both ETD and ECD [23]. Under native ETD and ECD conditions, 15% (in the best case) of the -SO 3 modification retainment was observed for the multiply protonated cations [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation